The Effect of Sonication Time on the Properties of Electrically Conductive PANI/Sago Starch Blend Prepared by the One-Pot Synthesis Method - Ali Mohsin, M. E.; Shrivastava, Nilesh K.; Basar, Norazah; Arsad, Agus; Hassan, Azman (Frontiers in Materials, 2019)
This study is part of ongoing research on the preparation of electrically conductive and physically stable Polyaniline/Sago starch (PANI/Sago) blend films using a simple one-pot synthesis method. The synthesis of PANI in the presence of Sago to prepare the PANI/Sago blend was done via in situ polymerization using ultrasound irradiation. For in situ polymerization of PANI/Sago blends, ammonium persulfate (APS) was used as an oxidant while hydrochloric acid (HCl) acted as a dopant. The effect of sonication time (0.5–5 h) on the structural properties (1H NMR and FT-IR), electrical conductivity (E.C), optical properties (UV-VIS), and the morphological (FE-SEM) and thermal stability (TGA) of the prepared PANI/Sago blends was studied. 1H NMR and FT-IR results revealed that the polymerization of PANI/Sago for more than 2 h leads to the disintegration/deformation of Sago starch due to excessive kinetic energy generated via the continuous collapsing of cavitation bubbles. In addition to the findings about Sago starch, FT-IR analysis also revealed the dominance of PANI property for the blend sonicated for 2 h as it contains a sharp and intense PANI peak at 1,500 cm−1, which represents the stretching vibration of benzenoid ring. 1H NMR and FT-IR results were found to be in compliance with E.C results, which showed the E.C of the blend sonicated for 2 h was highest. The UV-Vis results in combination with energy band values, thereby supporting the E.C results. The morphology of the prepared blends was found to be highly connected, which helps with good inter- and intra-chain electron transfers within the blends. The variation in sonication time seems to have very little impact on the thermal stability of the blends, as it was found that all blends were thermally stable up to 200°C, and only minor variation was observed beyond that.